Kebijaksanaan dan Kepuasan Hidup pada Remaja - Belladina N Raharja; Aisah Indati (Faculty of Psychology, Universitas Gadjah Mada, 2018)
Teenagers must meet their needs to get life satisfaction but if they cannot meet their needs then as a result teens can act negatively or they will still be satisfied with their lives. This study attempted to determine the relationship between wisdom and life satisfaction among adolescents. Participants in this study were 105 subjects. The study hypothesized that there was a positive relationship between wisdom and life satisfaction among adolescents. The data on this study was obtained by using Likert scales for Three Dimensional Wisdom Scale and Brief Multidimensional Student’s Life Satisfaction Scale. Finding suggests a significant positive relationship between wisdom and life satisfaction among adolescents.